A Study of CPU Scheduling Techniques in Comparison - Pinaki Pratim Acharjya, Santanu Koley, Subhabrata Barman, Rajesh Mukherjee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Due to the requirement to alter and test operating system kernel code and assess the resulting performance on a consistent workload of real applications, developing CPU scheduling methods and understanding their impact in practice can be challenging and time consuming. Because the processor is such a valuable resource, CPU scheduling is critical for achieving the operating system (OS) design goals. The goal should be to keep as many processes active as possible at all times in order to get the most out of the CPU. The primary goal of CPU scheduling is to improve the computer's performance. The amount of time spent waiting has a significant impact on the performance and execution time of a computer system. It's much easier to grasp what's going on inside the system with this representation, and why a different collection of processes is a candidate for CPU allocation at different periods. The study's goal is to examine the highly efficient CPU scheduler's impact on the design of high-quality scheduling algorithms that meet the scheduling goals. It is mostly focused on reducing waiting times and turn-around times in order to improve a computer system's level of performance. Many CPU scheduling methods exist, however due to high context switch rates, long waiting times, long response times, long turnaround times, and low throughput; they cannot be applied in real-time operating systems.